Moses Mendelssohn as an Influence on Hermann Cohen’s “Idiosyncratic” Reading of Maimonides’ Ethics - George Y. Kohler (Religions, 2023)
Surprisingly, there are at least three major theological subjects where Hermann Cohen seems to agree with Mendelssohn—against standard Jewish Reform theology. Even more interesting: All three points stand in connection with the religious thought of Moses Maimonides (1137–1204), the medieval halakhist and philosopher, whose radical theological ideas Mendelssohn mostly rejected and Cohen generally adopted. Should this observation be true, however, we might assume that Cohen took at least a few hints for his own reading of Maimonides from Mendelssohn. This conclusion would then in itself be surprising, because Cohen, contrary to the Jewish Reform theologians of the 19th century, and in fact contrary to everyone else, read Maimonides in what was generally called an “idiosyncratic” way: For Cohen, Maimonides was a proto-idealist, who often followed Plato much more than Aristotle, and who sometimes even anticipated Immanuel Kant. Even more exceptionally, for Cohen Maimonides’ philosophy in the Guide of the Perplexed was focused on a theology of ethics rather than on a metaphysics of knowledge of the divine. I will attempt to provide proof-texts showing that on these three points Mendelssohn and Cohen are essentially in harmony. Still, my proofs for a probable Mendelssohnian influence on Cohen depend on a very close reading of both Mendelssohn’s relevant passages, as well as of the corresponding texts in Maimonides.